KAJIAN PENGOLAHAN DAN DISTRIBUSI AIR MINUM PDAM GIRI MENANG - Jannah, Wardatul; Itratip, Itratip (Jurnal Ilmiah IKIP Mataram, 2018)
In this study a study of the processing and distribution of drinking water has been carried out in the Regional Company of Giri Menang Drinking Water (PDAM Giri Won). This study aims to determine the stages of processing and distribution of drinking water in the Winning Giri PDAM. The results showed that there were several stages in drinking water treatment that were in accordance with Indonesian National Standards namely the coagulation stage, the flocculation stage, the sedimentation stage (sedimentation), and the stage of water absorption (filtration). The water distribution process is carried out after going through the processing stage. Water distribution is adjusted to the list of water distribution recipients that have been registered with the Giri Winning PDAM